2020
DOI: 10.1055/s-0040-1709164
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Reoperation after Fusion and after Decompression for Degenerative Lumbar Spinal Stenosis: A Single-Center Experience of 987 Cases

Abstract: Background and Study Aim Reoperation for lumbar spinal stenosis (LSS) is technically challenging. Studies comparing preoperative risk factors and reoperation outcomes between spinal fusion and spinal decompression are limited. Thus this study compared fusion and decompression with respect to reoperation rates, preoperative factors related to re-surgery, and clinical outcomes. Patients and Methods This retrospective cohort study included prospectively collected data from patients who underwent revisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
(26 reference statements)
1
3
0
Order By: Relevance
“…by guest on September 18, 2022 http://ijssurgery.com/ Downloaded from a reoperation rate of 9.7%, while other studies have reported rates between 4% and 14.9%. [13][14][15] The reoperation rate for open discectomy in our cohort was 6.6%, corresponding to 5.6% to 9.8% in previous studies. 16,17 The most common cause of reoperation in our study population was infection, representing 28% of all reoperations.…”
Section: Notesupporting
confidence: 55%
“…by guest on September 18, 2022 http://ijssurgery.com/ Downloaded from a reoperation rate of 9.7%, while other studies have reported rates between 4% and 14.9%. [13][14][15] The reoperation rate for open discectomy in our cohort was 6.6%, corresponding to 5.6% to 9.8% in previous studies. 16,17 The most common cause of reoperation in our study population was infection, representing 28% of all reoperations.…”
Section: Notesupporting
confidence: 55%
“… 13 , 14 Blumenthal et al reviewed patients with symptomatic stenosis with grade I degenerative lumbar spondylolisthesis and found that incidence of reoperation was as high as 37.5% at a mean follow-up duration of 3.6 years. 9 The main deficit of open laminectomy is wide disruption of posterior supporting structures for segmental instability, while decompression combined with spinal fusion may cause complications such as proximal junctional kyphosis and pseudarthrosis, 29 which are all responsible for the such high incidence of reoperation. A systematic review and meta-analysis showed that fusion increased the risk of reoperation relative to decompression alone when treating LSS without spondylolisthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The continuous flushing function is conducive to controlling bleeding and providing a clearer surgical field of vision. UBED does not need a sleeve and will not restrict the use of instruments [ 43 ]. Conventional arthroscopic instruments and spinal open surgery instruments can be used, which can save costs [ 44 ].…”
Section: Discussionmentioning
confidence: 99%